AN ECONOMIC ANALYSIS OF FISHERIES AND MOLLUSCAN FISHERIES NEXUS IN PAKISTAN 1950-2014 - M. Mohsin; Y. T. Mu; A. Mehak; A. M. Memon; M. Noman; T. R. Pavase (Journal of Animal and Plant Sciences, 2019)
This is the first attempt to analyze Pakistani fisheries sector, in general, and molluscan fisheries sector, particularly, and their markets for the period 1947-2014 on an economic basis. This investigation includes landing as well as trade figures in terms of imports and exports. Since the independence, Pakistan’s economy has gone through many fluctuations due to indigenous and exotic shocks. These perturbations include the separation of East Pakistan in 1971, exponential population growth, nuclear testing in 1998 and political instability. In addition to these factors, fisheries sector also faced several distresses of its own such as onset of small-scale artisanal fisheries, lack of technologies, meager institutional development and lack of awareness among fishing communities. These factors have led to the collapse of fisheries sector. Consequently, overall fisheries in general and molluscan fisheries sector particularly experienced tremendous changes. It is noteworthy that the trade in terms of exports of fish and molluscs (including their products) were recorded maximum in 2013 (238,757 t) and 1999 (9,440 t), respectively. Overall fish landings steadily increased from 21,540 t (1950) to a peak of 612,444 t (1999) and declined afterward. Similarly, total molluscan landings also showed increasing trend from 49 t (1982) and peaked at 10,208 t (1999) but decreased afterward.
Keywords: molluscan fisheries; trade; economic analysis; Pakistan